2015
DOI: 10.1126/science.aac9407
|View full text |Cite
|
Sign up to set email alerts
|

Patrolling monocytes control tumor metastasis to the lung

Abstract: The immune system plays an important role in regulating tumor growth and metastasis. For example, classical monocytes promote tumorigenesis and cancer metastasis; however, how nonclassical “patrolling” monocytes interact with tumors is unknown. Here we show that patrolling monocytes are enriched in the microvasculature of the lung and reduce tumor metastasis to lung in multiple mouse metastatic tumor models. Nr4a1-deficient mice, which specifically lack patrolling monocytes, showed increased lung metastasis in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
395
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 399 publications
(408 citation statements)
references
References 45 publications
11
395
1
1
Order By: Relevance
“…The lung is maintained by suction with a force great enough to lessen the physiological motion into a level compatible with high-resolution dynamic microscopic imaging [18,24,28,29,[43][44][45][46][47][48][49][50]. In particular, the resolution reached using this technique recently permitted observation of dendritic cell dendrites (Figure 2d) [44] and patrolling monocytes controlling tumor metastasis to the lung [51].…”
Section: Suctionmentioning
confidence: 99%
“…The lung is maintained by suction with a force great enough to lessen the physiological motion into a level compatible with high-resolution dynamic microscopic imaging [18,24,28,29,[43][44][45][46][47][48][49][50]. In particular, the resolution reached using this technique recently permitted observation of dendritic cell dendrites (Figure 2d) [44] and patrolling monocytes controlling tumor metastasis to the lung [51].…”
Section: Suctionmentioning
confidence: 99%
“…In breast cancer models, classical monocytes are recruited to metastatic sites and promote extravasation and subsequent growth of cancer cells (8). In contrast, it was reported that patrolling monocytes prevent melanoma metastasis to the lung by recruiting NK cells (9). The prevailing view is that metastasis occurs as a late event in cancer progression (10).…”
Section: Introductionmentioning
confidence: 99%
“…PMo depend on the transcription factor N4a1 for their development from bone marrow precursors [4] and in pathological conditions they can respond to a variety of stimuli, contributing to resolution of inflammation [5]. In a recent study by Hanna et al [6], a new anti-tumoral function of PMo has been demonstrated in different models of murine metastasis. This function of mouse surveillance resulted in increased killing of metastatic cells by natural killer (NK) cells.…”
mentioning
confidence: 99%
“…In conclusion, the study by Hanna et al [6] by the tumor via a CCL2-mediated mechanism; they extravasate into the lung tissue where they differentiate into MAMs and interact with cancer cells, promoting their extravasation and the formation of micrometastasis. These recruited IMo differentiate into MAMs and secrete CCL3 that enhances their retention in the tissue.…”
mentioning
confidence: 99%